After Radical Trachelectomy: Reproductive and Obstetrical Outcomes of Fertility-Sparing Surgery for Cervical Cancer - Soltanizadeh, Sinor; Rosendahl, Mikkel; Frøding, Ligita Paskeviciute; Bjørn, Signe Frahm; Mosgaard, Berit Jul; Høgdall, Claus (Seminars in Reproductive Medicine, 2025)
Radical trachelectomy has become an accepted fertility-sparing treatment for patients with early-stage cervical cancer. Despite its oncological safety, radical trachelectomy is associated with persistent sexual dysfunction and voiding issues, complicating long-term quality of life. Fertility outcomes demonstrate overall pregnancy rates ranging from 25.7-73%, with less radical procedures such as conization and simple trachelectomy reporting higher pregnancy rates compared with radical trachelectomy. Assisted reproductive treatments might be necessary due to complications such as cervical stenosis. During pregnancy, there is an elevated risk of miscarriage, preterm delivery, and premature rupture of membranes due to cervical shortening. However, less radical fertility-sparing procedures such as conization and simple trachelectomy demonstrate lower preterm delivery rates. Prophylactic cerclage, as well as close monitoring of cervical length during pregnancy, is essential, and cesarean section remains the recommended method of delivery. Recent studies suggest that less radical fertility-sparing procedures may provide comparable oncological safety while reducing complications, highlighting the need to reevaluate surgical approaches. This review provides an overview of reproductive and obstetrical outcomes in patients after treatment for early-stage cervical cancer with trachelectomy. This review additionally emphasizes the need for further research to refine fertility-sparing strategies.
Keywords: cervical cancer; fertility-sparing surgery; pregnancy; obstetric; trachelectomy